2012
DOI: 10.1002/acr.21663
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab or a second anti–tumor necrosis factor therapy for rheumatoid arthritis patients who have failed their first anti–tumor necrosis factor therapy? Comparative analysis from the British Society for Rheumatology Biologics Register

Abstract: ObjectiveTo compare the effectiveness of rituximab (RTX) or a second anti–tumor necrosis factor (anti-TNF) therapy in rheumatoid arthritis (RA) patients who had failed their first anti-TNF and switched to either RTX or a second anti-TNF, in routine clinical practice.MethodsRA patients were registered with the British Society for Rheumatology Biologics Register. Response to treatment 6 months after switching was assessed using European League Against Rheumatism (EULAR) criteria and improvements in a Health Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 19 publications
6
33
1
6
Order By: Relevance
“…This simple observation suggests that genetic control of treatment response may be different for different drugs. This finding is consistent with the clinical observation that RA patients who fail one anti-TNF drug may still respond to a different anti-TNF drug, albeit at lower rates of response [19]. If confirmed in larger samples and more comprehensive analyses, then this could have major implications for how physicians prescribe these drugs.…”
Section: Discussionsupporting
confidence: 85%
“…This simple observation suggests that genetic control of treatment response may be different for different drugs. This finding is consistent with the clinical observation that RA patients who fail one anti-TNF drug may still respond to a different anti-TNF drug, albeit at lower rates of response [19]. If confirmed in larger samples and more comprehensive analyses, then this could have major implications for how physicians prescribe these drugs.…”
Section: Discussionsupporting
confidence: 85%
“…In clinical practice, many patients initiating RTX have lower disease activity levels compared with those enrolled in anti-TNF RCT, a factor that further influences evaluations of effectiveness 12,13,14 . Most observational data examining the effectiveness of RTX in routine clinical practice have been reported from European registries 15,16,17,18,19,20,21,22 , with scant information currently available from the United States 23 . There is tremendous value in examining US cohorts of patients with RA to assess effectiveness because of the differences in treatment practices and patient characteristics.…”
Section: Rheumatologymentioning
confidence: 99%
“…However, the evidence to support TNFi cycling is limited,12–15 and some studies have suggested that switching to a non-TNFi biologic is more effective than TNFi cycling 6,1618. Additional studies are needed,19 particularly as newer non-TNFi options such as sarilumab,20,21 sirukumab,22 and baricitinib2325 are expected to become available soon for RA treatment 26,27…”
Section: Introductionmentioning
confidence: 99%